Achievement Goal Orientation and Situational Motivation for a Low-Stakes Test of Content Knowledge - Waskiewicz, Rhonda A. (American Journal of Pharmaceutical Education, 2012)
Objective. To determine the extent of the relationship between students’ inherent motivation to achieve in a doctor of pharmacy program and their motivation to achieve on a single low-stakes test of content knowledge. Method. The Attitude Toward Learning Questionnaire (ATL) was administered to 66 third-year pharmacy students at the beginning of the spring 2011 semester, and the Student Opinion Scale (SOS) was administered to the same group immediately following completion of the Pharmacy Curricular Outcomes Assessment (PCOA). Results. Significant differences were found in performance approach and work avoidance based on situational motivation scores. Situational motivation was also found to be directly correlated with performance and mastery approaches and inversely correlated with work avoidance. Criteria were met for predicting importance and effort from performance and mastery approaches and work avoidance scores of pharmacy students. Conclusions. The ability to predict pharmacy students’ motivation to perform on a low-stakes standardized test of content knowledge increases the test’s usefulness as a measure of curricular effectiveness.